ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH PERIODE 2010-2014 - Yuliani Purnamasari, Gusti Ayu; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
This study aims to determine the effect of CAR, NPL, NIM and LDR on performance comparison of the financial performance of banks and conventional banks listed on the Stock Exchange and banks syraiah listed in the FSA. The data used in this study were obtained from published financial statements of companies listed on the conventional banking and Islamic banking BEI listed in the FSA from the year 2010-2014 with a total population of 31 companies and 11 conventional banking Islamic banking. The data analysis technique used is multiple linear regression with SPSS applications. Based on the analysis in conventional banks showed that partially CAR and NIM positive effect on ROA, NPL negative effect on ROA, and LDR do not affect the ROA. Furthermore, the Islamic banks partially CAR and LDR positive effect on ROA, NPL negative effect on ROA and NIM no effect on ROA. The results of different test analysis showed no significant differences between the financial performance of conventional banks and Islamic banks.
Keywords: ROA, CAR, NPL, NIM, LDR